2022
DOI: 10.3389/fneur.2022.836796
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Digital Health Intervention for Vestibular Rehabilitation: Usability and Subjective Outcomes of a Novel Platform

Abstract: Digital technologies are increasingly available and are reducing in cost. There is an opportunity to move to a digital health approach in vestibular rehabilitation (VR), but there is a paucity of suitable systems available and a consequent lack of evidence to support their use. This study aimed to investigate a novel digital platform developed specifically for VR (comprising clinician software, a wearable sensor, and a patient-facing app). Participants (n = 14, 9F:5M, mean age 59) with vestibular dysfunction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…D'Silva et al reported that their older female participants (aged 60–74 years) found that the Vestibular Rehabilitation App TM was easy to learn in a single session, the game format was enjoyable due to the graphics and colors, the score was motivating, and the game feedback would improve performance ( 27 ). Likewise, Meldrum et al reported that participants with dizziness (mean age = 59 years, range: 38–76 years) found a digital VRT app to be easy to use (SUS = 82.7 = A), useful in learning about their vestibular condition, and enjoyable due to the color scheme and clear layout ( 28 ). Developers of technology based VRT, do need to consider adult preferences in their game design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D'Silva et al reported that their older female participants (aged 60–74 years) found that the Vestibular Rehabilitation App TM was easy to learn in a single session, the game format was enjoyable due to the graphics and colors, the score was motivating, and the game feedback would improve performance ( 27 ). Likewise, Meldrum et al reported that participants with dizziness (mean age = 59 years, range: 38–76 years) found a digital VRT app to be easy to use (SUS = 82.7 = A), useful in learning about their vestibular condition, and enjoyable due to the color scheme and clear layout ( 28 ). Developers of technology based VRT, do need to consider adult preferences in their game design.…”
Section: Discussionmentioning
confidence: 99%
“…Experienced VRT clinician participants felt that a VRT app should include features to record and track head/eye movement, monitor symptoms, score the accuracy of task performance, and measure and improve adherence to a prescribed home exercise program. Despite clinicians' desire to be able to track both head and eye movements, to date most VRT apps only monitor head movement ( 27 , 28 ); thus, the ability to assess accurate performance of gaze stabilization exercises is limited. To the best of our knowledge, VestAid is the only other VRT system in development to monitor eye movement ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, telemedicine -with the recent covid-19 pandemic -is getting more attention than ever before [48][49][50]. The benefits include making healthcare more accessible and reducing patient costs.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcomes included improvement of quality of life measured with the Dizziness Handicap Inventory (DHI) [46] and psychological impairments such as anxiety and depression measured with the Patient Health Questionnaire (PHQ) subscale [47], Hospital Anxiety and Depression Scale (HADS) [48][49][50], Generalized Anxiety Disorder assessment (GAD-7) [51] and Beck Depression Inventory Scale (BDI-II) [52,53]. More in detail, the Dizziness Handicap Inventory (DHI) and Vertigo Symptom Scale-short form (VSS-SF) are among the most commonly cited PRO instruments in clinical vestibular research [54], with the former one widely used even in the clinical context [41]. Whilst DHI explores each of the three ICF domains (activity, participation, body function and structures), VSS-SF focuses only on "body functions and structures" [54].…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…While there is an increasing number of available studies on the evaluation [36,37] and management of dizziness through telemedicine [38,39], systematic reviews investigating the effectiveness of telerehabilitation in dizziness are still lacking, despite promising prospects [40,41] and the spread of TR services [27,28]. Therefore, this systematic review had two primary objectives: firstly, to provide an up-to-date overview of the topic, and secondly, to conduct a quantitative assessment of the effectiveness of telerehabilitation in treating dizziness.…”
Section: Introductionmentioning
confidence: 99%